Improvement of gm/ID method for detection of self-heating effects - Mori, C. A.B.; Agopian, P. O.D. [UNESP]; Martino, J. A. (The Electrochemical Society, 2018)
This paper presents an improvement on the use of the transistor efficiency to verify the presence of self-heating effects using only DC measurements. Applying this improved method on FinFET devices allowed the establishment of a comparison of the self-heating effect among devices with different channel lengths, despite their different channel length modulation effects.